Paediatric traumatic brain injury. Issue 6 (December 2019) - Coulter, Ian C.; Forsyth, Rob J.
Abstract : Purpose of review: To provide a summary of recent developments in the field of paediatric traumatic brain injury (TBI). Recent findings: The epidemiology of paediatric TBI with falling rates of severe TBI, and increasing presentations of apparently minor TBI. There is growing interest in the pathophysiology and outcomes of concussion in children, and detection of 'significant' injury, arising from concern about risks of long-term chronic traumatic encephalopathy. The role of decompressive craniectomy in children is still clarifying. Summary: Paediatric TBI remains a major public health issue.